(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the author examines the possibility of using international and foreign experience in legal regulation of environmental business in the Republic of Kazakhstan. In the modern period of the Republic of Kazakhstan is at an important stage of its development – the transition to a «green economy» and on the eve of preparations for the international exhibition «EXPO-2017» entitled «Energy Future», as well as the implementation of the Partnership Programme «Green Bridge» to promote Sustainable Development in Central Asia and other regions of the world. After an overview of the use of international and foreign experience in legal regulation of environmental business in the Republic of Kazakhstan, a number of conclusions were made. Key words: ecology, law, environment, security, green economy.